2019
DOI: 10.1590/1980-265x-tce-cicad-13-5
|View full text |Cite
|
Sign up to set email alerts
|

Perception of Damage and Benefits Associated to the Use of Marijuana in Adolescents, Viña Del Mar, Chile

Abstract: Objective: analyze the perception of harm and benefits, and its association with the use of marijuana in high school students, as well as the intention to use it in a context of regulatory changes. Method: a quantitative, exploratory, cross-sectional study was designed, applying a self-administered questionnaire to 268 high school students. Results: The results showed that the declared consumption in the sample is higher than that obtained in previous studies in Chile, which had already warned of the increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
0
0
0
1
Order By: Relevance
“…Regarding the use of marijuana, a study carried out in Viña Del Mar, Chile, with 268 high school students, found that 52% of the participants admitted to having used marijuana at some point in their lives 15 . There is an association between marijuana use and school problems, with an average age of first experimentation of 15.7 years 16 .…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the use of marijuana, a study carried out in Viña Del Mar, Chile, with 268 high school students, found that 52% of the participants admitted to having used marijuana at some point in their lives 15 . There is an association between marijuana use and school problems, with an average age of first experimentation of 15.7 years 16 .…”
Section: Discussionmentioning
confidence: 99%
“…Actualmente existe un aumento de la prevalencia del uso de cannabis a nivel mundial, así como una disminución de la percepción de riesgo asociado a la misma (Degenharlt et al, 2016;Tapia & Khenti, 2019;Rodriguez & Khenti, 2019). Hay una alta prevalencia de uso en América del Norte y un aumento gradual desde 2007 (Trigo et al, 2018).…”
Section: Aspectos Epidemiológicos Del Abuso Y Dependencia a Cannabisunclassified